Measurement and Simulation of the Counting Efficiency of a Whole-body Counter Using a BOMAB Phantom Inserted with Rod Sources Containing Mixed Radionuclides. Issue 3 (March 2018) - Park, MinSeok; Yoo, Jaeryong; Ha, Wi-Ho; Park, Sunhoo; Jin, Young Woo
Abstract : Abstract: The examination of internal contamination is important for providing an adequate medical response during a radiological emergency. A whole-body counting system can assess gamma-emitting radionuclides in a human body when monitoring internal contamination. It is necessary to calibrate whole-body counting systems by using a calibration phantom, such as a Bottle Manikin Absorption phantom, to properly assess internal contamination. However, the total weight of the Bottle Manikin Absorber phantom is high, and there can be leakage of radioactive sources, which are disadvantages of using such a phantom. This study proposes a calibration phantom that is designed to overcome these disadvantages. The proposed phantom consists of rod sources that are inserted in each part of the phantom. The counting efficiency of the rod-source-inserted calibration phantom was acquired using a Monte Carlo simulation method, but the results were evaluated by comparing the experimental efficiencies with those of a conventional Bottle Manikin Absorption phantom by using two commercial whole-body counting systems (stand-up type and bed type). The efficiency curve of the rod-source-inserted phantom matched well that of the conventional calibration phantom. The relative deviation between the efficiencies of the conventional Bottle Manikin Absorption phantom and the proposed calibration phantom in both whole-body counting systems was less than 11%, and the total weight of the phantom was also reduced. These results suggest that the proposed phantom can be manipulated more easily and replace the conventional Bottle Manikin Absorption calibration phantom for these two types of whole-body counting systems.